#### Answer

LCD=2$x^{2}$(x+4)(x-4)

#### Work Step by Step

$\frac{1}{x^{2}-16}$, $\frac{x+6}{2x^{3}-8x^{2}}$
$x^{2}$-16=$x^{2}$-$4^{2}$=(x+4)(x-4)
2$x^{3}$-8$x^{2}$=2$x^{2}$(x-4)
LCD=2$x^{2}$(x+4)(x-4)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

LCD=2$x^{2}$(x+4)(x-4)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.